Purification, structural characterization, and bioactive properties of exopolysaccharides from Saccharomyces cerevisiae HD-01 - Yang, Ruoxi; Liu, Lina; Gao, Dongni; Zhao, Dan (Frontiers in Bioengineering and Biotechnology, 2024)
Exopolysaccharides (EPSs), which show excellent biological activities, like anti-tumor, immune regulation, and anti-oxidation activities, have gained widespread attention. In this study, an EPS-producing Saccharomyces cerevisiae HD-01 was identified based on 18S rDNA sequence analysis and an API 20C test. The purified HD-01 EPS was obtained by gel filtration chromatography. High-performance liquid chromatography (HPLC), gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FT-IR), and nuclear magnetic resonance (NMR) revealed that it was a heteropolysaccharide composed of α-1 (38.3%), α-1, 2 (17.5%), α-1, 6 (14.8%)-linked mannose and α-1, 2, 3, 6 (24.3%), α-1 (3.3%), β-1, 4 (1.8%)-linked glucose. Chemical composition and elemental analysis indicated the existence of sulfation modifications. A scanning electron microscope (SEM) and an atomic force microscope (AFM) revealed that it exhibited a flaky structure with thorn-like protrusions on the three-dimensional surface. X-ray diffraction (XRD) revealed that it was an amorphous non-crystalline substance. HD-01 EPS had great thermostability; probiotic properties; strong antioxidant properties to DPPH, ABTS, and hydroxyl; and good reducing power. The MTT, NO, and neutral red assays demonstrated that it had a great immunomodulatory effect on macrophages RAW264.7. All results suggested that the HD-01 EPS had the potential to be applied in the food and pharmaceutical fields.